The emperor's clothes : a personal viewpoint on politics and administration in the imperial Ethiopian government, 1941-1974 - Gaitachew Bekele (African series (East Lansing, Mich.) ;, 1993)
An engaging personal account of a public service career n the period leading to the 1974 revolution. It ...persuades and provides real insight into the genuine noblesse oblige of the first generation of technocrats drawn from the social elite of the post- war period.